Synthesis and characterization of a new heterocyclic azo pigment - Asniza .M; Issam .A.M; Abdul Khalil .H.P.S (Universiti Kebangsaan Malaysia, 2011)
A new heterocyclic coupling agent has been produced from the reaction of maleic anhydride and p-aminophenol, namely N-(4-hydroxylpheneyl)maleimide. The coupling agent underwent azo coupling reaction with aromatic amine, which is p-aminophenol to produce a new heterocyclic azo pigment. The pigment was then subjected to solubility, hiding power and light fastness test. Fourier Transform Infrared Spectroscopy (FTIR), Ultraviolet/Visible (UV/Vis) Spectroscopy, and Nuclear Magnetic Resonance Spectroscopy (1H-NMR, 13C-NMR) were used to obtain the characteristics and structural features of the pigment.